(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The National Education Policy 2020 aims to significantly expand vocational education opportunities for students in India. The plan is for at least half of all learners in schools and higher education to have some form of exposure to vocational skills and training by the year 2050. Career counselling and vocational guidance services could play a pivotal role in helping realize the objectives of increasing exposure to vocational education, as outlined in the NPE 2020. However, the guidance provided may not impact all students equally. Present paper aims to investigate how effectively vocational guidance impacts the career choices of grade 12 students. This study uses a descriptive survey design and the data is collected using questionnaire instrument. 116 students (56 boys and 60 girls) constituted the sample for the study. Frequency count and mean calculation was used to answer the research questions and the hypothesis was tested using independent samples t-test with a significance level of 0.05. The findings of the study revealed that vocational guidance has been greatly successful in shaping the career choices of students selected for the study. Additionally, the results showed that vocational guidance had a substantially different impact on career choices between urban and rural students. Additionally, no significant difference in the impact made by vocational guidance on students based on gender was observed. The study therefore recommends that all high schools should have career counsellors and students should be made aware of the value of guidance services so they can make well-informed career choices.